Beyond theory : changing organizations through participation - Toulmin, Stephen, 1922-2009; Gustavsen, Bjørn (Dialogues on work and innovation, 1996)
Action Research is one of the most practical and down-to-earth ways of doing research into working life. Beyond Theory draws on examples and actual cases to discuss action research within the framework of the modern, and postmodern, theory of science debate. While action research has been much criticized by the traditionalists, the book reflects a convergence between action research and positions emerging out of the critique of scientific traditionalism. Discussions between these two fields of knowledge, originally so very different, can enrich both. The book will be useful not only to researc.